Enhancing microalga Chlorella sorokiniana CY-1 biomass and lipid production in palm oil mill effluent (POME) using novel-designed photobioreactor. Issue 1 (1st January 2020) - Cheah, Wai Yan; Show, Pau Loke; Yap, Yee Jiun; Mohd Zaid, Hayyiratul Fatimah; Lam, Man Kee; Lim, Jun Wei; Ho, Yeek-Chia; Tao, Yang
ABSTRACT: Chlorella sorokiniana CY-1 was cultivated using palm oil mill effluent (POME) in a novel-designed photobioreactor (NPBR) and glass-made vessel photobioreactor (PBR). The comparison was made on biomass and lipid productions, as well as its pollutants removal efficiencies. NPBR is transparent and is developed in thin flat panels with a high surface area per volume ratio. It is equipped with microbubbling and baffles retention, ensuring effective light and CO2 utilization. The triangular shape of this reactor at the bottom serves to ease microalgae cell harvesting by sedimentation. Both biomass and lipid yields attained in NPBR were 2.3–2.9 folds higher than cultivated in PBR. The pollutants removal efficiencies achieved were 93.7% of chemical oxygen demand, 98.6% of total nitrogen and 96.0% of total phosphorus. Mathematical model revealed that effective light received and initial mass contributes toward successful microalgae cultivation. Overall, the results revealed the potential of NPBR integration in Chlorella sorokiniana CY-1 cultivation, with an aim to achieve greater feasibility in microalgal-based biofuel real application and for environmental sustainability. Graphical abstract: